Respuesta :

Answer:

Step-by-step explanation:

Rewrite this in standard quadratic equation form:  x^2 - 7x +  6 + 8 = 0, or x^2 - 7x + 14 = 0.  This does not factor easily, so I will use the quadratic formula to find the roots and then write out the factors based upon the roots:

The discriminant is b^2 - 4ac, which here is (-7)^2 - 4(1)(14) = -7.

Because the discriminant is negative, we know that there are two unequal, complex roots.  They are:

      -(-7) ± i√7         7 ± i√7

x = ----------------- = ---------------

              2                     2

One factor is (x - [1/2]{7 ± √7}  )